(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article reveals the nature of the concept «the linguistic personality, the structure of the linguistic personality» is characterized, the psychological reasons of language teaching are also revealed here.